Incorporation of Yogurt Acid Whey in Low-Lactose Yogurt Ice Cream - Lambros Sakkas; Marianna Karela; Evangelia Zoidou; Golfo Moatsou; Ekaterini Moschopoulou (Foods, 2023)
Yogurt acid whey (YAW), a by-product of strained yogurt production, is a strong environmental pollutant because of its high organic load. Hence, efforts are made for its utilization to minimize its disposal in the environment. This study deals with the incorporation of YAW in yogurt ice cream (YIC) by partial replacement of yogurt with simultaneous lactose hydrolysis (LH) of the formulated YIC mix. Six YIC mix formulations were made, two without YAW (non-LH- and LH-control samples, A and AH), two with 12.5% YAW (samples B and BH), and two with 18.75% YAW (samples C and CH). The results showed that the partial replacement of yogurt with YAW decreased significantly (p < 0.05) the total solids of B, BH, C, and CH products (31.72 ± 0.14%, 31.92 ± 0.21%, 30.94 ± 0.14%, and 31.27 ± 0.10%, respectively) compared to the total solids of control products A and AH (33.30 ± 0.36% and 33.74 ± 0.06%, respectively). In contrast, the overruns increased (51.50 ± 2.36%, 58.26 ± 0.09%, 56.86 ± 1.92%, and 65.52 ± 1.30% for the B, BH, C, and CH products, respectively) compared to control samples (42.02 ± 2.62% and 49.53 ± 2.12% for A and AH, respectively). LH significantly decreased the freezing point and the viscosity of the YIC mixes but increased the overruns of the products as shown previously. YAW significantly decreased the hardness of the B and C products (56.30 ± 2.11 N and 43.43 ± 3.91 N, respectively) compared to control A (81.14 ± 9.34 N), and LH decreased it even more, leading to a rather soft scoop YIC. AH, BH, and CH YICs exhibited better melting properties despite the lack of fat destabilization in all samples. After 60 days of storage, counts of yogurt starter microorganisms were still >107 cfu/g and DPPH radical scavenging activity had increased in all products. In the sensory evaluation test, lactose-hydrolyzed samples AH, BH, and CH had less intense sandiness and, as expected, more intense sweetness. In conclusion, in the framework of the circular economy, it is possible for the YAW to be used as a resource material at a ratio of 12.5% to produce a YIC product without leaving behind any new waste.